Estudo piloto dos impactos antrópicos do Rio Pará na Praia de Carananduba e do Rio Cajueiro na Ilha de Mosqueiro em Belém-Pa (Brasil) - JESUS, Anderson Haroldo Louzada de (2023)
Continental aquatic ecosystems and marine ecosystems are being extensively altered in their structure by anthropogenic impacts, producing substantial changes in land use, air pollution, with impacts on surface and underground water resources. These impacts are global, regional, and local and range from climate changes and climate variations to the deforestation of ciliary forests, changes in river flow and the introduction of exotic species. Assessment of anthropogenic impacts of Carananduba Beach on the Pará River and Cajueiro River in the Metropolitan Region of the Mosqueiro district. Methodology: field research, with in locus analyses using qualitative and quantitative methods, in water collection on Carananduba beach on Mosqueiro Island in Belém - PA and observational, in Carananduba and Cajueiro river, in aspects of environmental morphology, urban occupation and anthropogenic impacts, occupation of riverbanks, characteristics of urban sewage on the beach limits, local commerce and resulting environmental impacts. urbanisation and environmental impacts, sewage and urban waste in the area of the Pará and Cajueiro rivers. Water samples were collected, and qualitative chemical analysis was carried out in situ on Carananduba beach to identify the possible presence of heavy metals. Conclusions: The impacts on Carananduba beach and in the area of the bridge over the Cajueiro River, which cause environmental disequilibrium, are anthropogenic, especially due to the occupation and use of areas without basic sanitation infrastructure and correct waste removal, causing impacts that are still reversible at the moment. Traces of hexavalent copper, a potential cause of dermatitis, were found on Carananduba beach. However, more samples need to be collected to identify whether the source is seasonal or perennial, to intervene with measures that can eliminate or mitigate its occurrence. There is an urgent need to implement environmental education policies for the community, sewage treatment and urban waste collection.